Application of centrifugal filter to aerosol size distribution measurement. Issue 11 (2nd November 2017) - Tanaka, Yutaka; Choi, Hyun-Jin; Shimadzu, Kosuke; Higashi, Hidenori; Seto, Takafumi; Kumita, Mikio; Otani, Yoshio
ABSTRACT: In the present work, the centrifugal filter proposed by the authors was applied to classify aerosol particles followed by the detection of total mass or number concentrations so as to measure the size distribution of aerosol particles. The structure and operating condition of the centrifugal filter were optimized in order to attain sharp separation curves with various cut-off sizes between 0.3 and 10 μm. The aerosol penetrating the centrifugal filter at various rotation speeds was measured with a photometer to determine the total mass concentration. The virtue of this system is that the cut-off size is varied just by scanning the rotation speed of filter and that it can be applied to the measurement of high concentration aerosols without dilution by choosing an appropriate filter medium. As a result, the centrifugal filter was successfully applied to measure the size distribution of solid particles in size ranging from 0.3 to 10 μm. Copyright © 2017 American Association for Aerosol Research